Pengembangan Program Pemberdayaan Masyarakat Berbasis Teknologi di Desa Wukirsari Cangkringan Sleman - Sari Ningsih, Dyah (STAI Terpadu Yogyakarta, 2024)
This community service program aims to develop a technology-based empowerment program in Wukirsari Village, Sleman. The objectives of this program are to explore how technology can be used as a tool for community empowerment, identify the challenges faced in the development of technology-based empowerment programs, and evaluate the impact of technology implementation on improving the quality of life in Wukirsari Cangkringan Village. The method used in this program includes workshops, training, and seminars focused on improving digital literacy and the use of technology in various sectors such as agriculture and small-medium enterprises (SMEs). Data analysis was conducted through qualitative and quantitative methods, assessing the success of the program through community engagement, technological adoption, and improved economic conditions. The results show that technology has played a significant role in enhancing agricultural productivity and expanding market access for local SMEs. However, challenges such as limited infrastructure and varying levels of digital literacy still need to be addressed. The findings suggest that while technology can greatly improve the quality of life in rural areas, further efforts are needed to ensure sustainable implementation through continuous training and improved infrastructure. The implications of this program highlight the importance of technology in rural development and the need for tailored strategies to overcome barriers to technology adoption.